A numerical investigation of the airfoil-gust interaction noise in transonic flows: Acoustic processes. (7th July 2018) - Zhong, Siyang; Zhang, Xin; Gill, James; Fattah, Ryu; Sun, Yuhao
Abstract: The sound produced by airfoil-gust interaction is a significant source of broadband noise in turbofan engines or contra-rotating open rotors (CRORs). There are competing mechanisms in this regime because of the presence of shocks that were seldom considered in the previous subsonic studies. A numerical investigation of airfoil-gust interaction noise at transonic speeds is undertaken in this work. By introducing vortical gust/synthetic turbulence to specified regions in the computational domain to interact with different elements in the flow field, it is shown that the dominant sound source is caused by leading edge-gust interaction. It is demonstrated that both streamwise and transverse disturbances interact with the near-field non-uniform mean flow and shocks can produce sound using a local gust injection method. The propagation of sound is significantly influenced by the presence of the shocks, and the far field radiation pattern is changed. We also study the effect of gust strength on the near and far field properties. The linearity is maintained for gust strength smaller than 1.0 % of the mean flow velocity. Otherwise, the shocks may experience oscillations that will alter the near-field aerodynamics and far-field radiation.